Normative Results of Healthy Older Adults on Standard Clinical Vestibular Tests - Davalos-Bichara, Marcela (2014)
OBJECTIVE: To describe the performance of healthy older adults on common clinical vestibular tests. PATIENTS: Fifty community-dwelling older adults aged 70 and older, with mean age of 77.2 ± 6.1 years and range of 70 to 95 years. INTERVENTION(S): Clinical vestibular tests, including spontaneous and head-shaking nystagmus, head impulse test (HIT), bucket test of subjective visual vertical, modified Romberg test (MRT), and Dizziness Handicap Inventory (DHI). MAIN OUTCOME MEASURE(S): Prevalence of abnormal vestibular tests and DHI score. RESULTS: We observed a 36% and 44% prevalence of abnormal right and left horizontal HIT, respectively. The bucket test was abnormal in 18% of participants; head-shaking nystagmus was present in 2%, and no participant had spontaneous nystagmus. Approximately 68% of participants had abnormal MRT. Abnormal horizontal HIT and MRT were significantly more prevalent among individuals age 80 years and older compared with those age 70 to 79 years (p < 0.05). Mean DHI score was 5.6 ± 11.2, consistent with no self-reported dizziness handicap. CONCLUSION: This study documents the expected performance of normative older adults on vestibular tests commonly administered in the neurotology clinic. We observed a high prevalence of abnormalities on clinical vestibular testing in healthy older adults, although self-perceived dizziness handicap was low. Further studies using newly available clinical testing methods (e.g., video HIT) may identify finer gradations of vestibular function in older individuals and the levels of vestibular loss associated with functional impairment.